Analyzing Vehicle-Pedestrian Conflicts at Satdobato Intersection - Deuja, Aayushma; Pandeya, Apekshya; Pandey, Pradipti; K.C., Sajana; Tiwari, Sushma; Gupta, Vibek (International Journal on Engineering Technology, 2026)
This study examines vehicle–pedestrian conflicts at the Satdobato signalized intersection in Lalitpur, Nepal, a critical urban node characterized by high-volume mixed traffic and high pedestrian activity. Utilizing primary data gathered via three-day video-based field surveys, the research captured peak-hour traffic volumes, pedestrian movements, and signal timings to develop a microscopic simulation model within VISSIM. Following calibration and validation against field conditions, conflict analysis was performed using the Surrogate Safety Assessment Model (SSAM), specifically employing Time to Collision (TTC) and Post Encroachment Time (PET) as primary indicators. The results reveal a high frequency of conflicts peaking at 2,680 incidents during the morning rush primarily driven by signal violations and inadequate pedestrian infrastructure. The study evaluates two mitigation strategies: redirecting pedestrians from Mahalaxmi lane to an existing overhead crossing, yielded a 13.88% reduction in conflicts; and construction of a new overhead crossing at Gwarko lane, achieved a more substantial 39.74% reduction. These findings demonstrate that targeted infrastructural interventions can significantly enhance intersection safety, though their efficacy remains contingent upon the specific operational characteristics of the diverse vehicle types present in the traffic stream.